Influence of technical processing units on the α-carotene, β-carotene and lutein contents of carrot (Daucus carrot L.) juice - Tingting Ma; Chengrui Tian; Jiyang Luo; Xiangyu Sun; Meiping Quan; Cuiping Zheng; Jicheng Zhan (Journal of Functional Foods, 2015)
The effects of four processing units on the contents of α-carotene, β-carotene and lutein in carrot juice were investigated. The results indicated that composite phosphate peeling exhibited the best peeling effect and led to the lowest loss of carotenoids among the four peeling methods. The best blanching conditions included a blanching temperature of 86 °C for 10 min and an addition of 0.25% of ascorbic acid. A certain range of blanching times and blanching temperatures contributed to the dissolution and stability of the three carotenoids, while excessive blanching temperatures and blanching times led to the degradation of the carotenoids. Single enzyme treatment or mixed enzyme treatment with different orders of addition could significantly raise the contents of the three carotenoids in the juice. However, the use of pectinase and cellulase at the same time exhibited an antagonistic effect. High temperature sterilization increased the loss of carotenoids in carrot juice on one hand but, conversely, improved its stability during storage.